Ex vivo Evaluation of the Dynamic Morphometry of the Caudal Cervical Intervertebral Disc Spaces of Small Dogs and Cats - Knell, Sebastian C.; Smolders, Lucas A.; Pozzi, Antonio (Frontiers in Veterinary Science, 2021)
The objective of this study was to provide a morphometric description of the caudal cervical intervertebral disc (IVD) spaces of small-breed dogs and cats. Specimens consisting of C4 through C7 from five small-breed dogs and six cats were positioned in neutral, flexion, extension, and lateral bending positions; and CT images were acquired. Height and width of the cranial and caudal vertebral endplates (VEPs), angle between the VEPs (IVD wedge angle), and craniocaudal distance (IVD width) between VEPs for the four loading positions were measured and compared for three segments (C4–C5, C5–C6, and C6–C7). VEP size normalized to body weight from medium-sized dogs was retrieved from a previous study and compared with data from small dogs and cats. A linear mixed model was used to compare outcome measures. Significance was set to p < 0.05. VEP size normalized to body weight was the largest in small dogs compared with cats (p = 0.0422) and medium-sized dogs (p = 0.0064). Cats and medium-sized dogs were similar (p = 0.2763) in this regard. Flexion and extension induced a reduction of IVD width in the ventral portion of the IVD and the area of the nucleus. The dorsal part of the IVD remained unchanged throughout loading conditions. Unique morphometric characteristics of the caudal cervical IVD space of small dogs and cats were detected that are different from those described in sizes of dogs (medium-sized) typically affected by caudal cervical spondylomyelopathy (CSM). These findings may help to understand the different pathomechanisms in cervical spinal disease between small- and medium-sized dogs, including caudal CSM.